ANALISIS HUKUM PIDANA TERHADAP NAHKODA YANG MENGANGKUT BARANG IMPOR SECARA MELAWAN HUKUM MENURUT UNDANG-UNDANG NO. 17 TAHUN 2006 TENTANG KEPABEANAN (STUDI PUTUSAN PENGADILAN NEGERI TANJUNG BALAI NOMOR 77/Pid.B/2017/PN-Tjb) 147005126/HK - Gibson Parsaoran; Alvi Syahrin; Mahmud Mulyadi; Sutiarnoto Sutiarnoto (Inspiring Law Journal, 2026)
Efforts to eradicate smuggling of imported goods have long been an interesting study material among law enforcers, because they are related to several agencies that have the authority and supervision over the implementers of the import and export. This issue should be quickly addressed because this problem has become one of the main targets in the implementation of the duties of law enforcers and several related agencies that have authority and supervision over the implementation of import and export of goods. One of the efforts to eradicate the transportation of imported goods unlawfully is with the judge's decision in combating criminal acts in the customs field. Judge's decision is the product of a court which is included in the judicial power section based on Article 24 of the third amendment to the 1945 Constitution which confirms that the judicial power is an independent power in carrying out judiciary to enforce law and justice carried out by the Supreme Court and judicial bodies which there are below such as general justice and so on.The research method used in this study is normative legal research, namely research carried out based on the main legal material by examining theories, concepts, legal principles and legislation relating to this research.Research Results and Discussion are: 1) The crime of smuggling is regulated in the provisions of Article 102, Article 102 A, and Article 102 B of customs laws. 2) Parties that can be held accountable according to the customs law are Individuals; Acting Director General of Customs and Excise; Carrier of Goods; Employers of Customs and Legal Services Management (Companies, Companies, Collections, Foundations, and Cooperatives). 3) Judges in Decision Number 77 / Pid.B / 2017 / PN-Tjb see factors affecting the skipper transporting imported goods unlawfully. These factors are personal character, mental pressure, the motives of the perpetrators and the state of the environment around the place of residence. However, judges at the Tanjung Balai District Court as in some of their decisions tend to forget and leave the effects of smuggling imported goods